Thermo-physical Properties of Graphite Powder and Polyethylene Modified Asphalt Concrete - Ahmad M.; Al-Dala'ien R.N.S.; Beddu S.; Itam Z.B. (Engineered Science Publisher, 2023)
Energy harvesting using asphalt solar collector has opened new era for the researcher and this study is an attempt to understand the thermo-physical properties of asphalt concrete. Study mainly focuses on the thermo-physical properties such as thermal conductivity, specific heat capacity, thermal diffusivity, thermal effusivity and density of asphalt concrete relation with thermal properties. Asphalt concrete incorporated with graphite powder 2.0%, 3.0%, 4.0%, 5.0% and 6.0% by weight of quarry dust, polyethylene (PE) content was optimized 9.0% used dry method of mixing, granite coarse aggregate size asphalt concrete (AC-14) and bitumen 60/70 (4.5%) used to prepare the Marshall. Firstly, Marshall Stability optimization was evaluated and the best performing Marshall Samples were produced to further analyze the thermal properties. Fox-50 steady state heat flow meter was used to determine the thermal properties of the graphite polymer asphalt concrete (GPAC). Study found that graphite polymer asphalt concrete density decreased in the result thermal conductivity, specific heat capacity, thermal diffusivity and thermal effusivity increased. In the conclusion, graphite polymer asphalt concrete thermal properties have increased and by increasing the temperature thermal physical increased though. Engineered Science Publisher LLC 2022